Grupos sanguíneos ABO y Rh y proteínas séricas en una población amerindia, Matambú, Costa Rica - Barrantes, Ramiro (1985)
Genetic structure of the population of Matambú, Costa Rica, was investigated using 6 genetic markers: ABO and Rh blood groups, and 4 serum proteins: albumin, ceruloplasmin, haptogIobin and transferrin. All the individuals were Rh+ and the l° allele had a high frequency (0.89). There are 4 polimorphic alleles in ceruloplasmin, including a possible new variant (3.8%). Transferrin Dchi had a remarkably high frequency (0.11). These results indicate that this group is of Amerindian origin, although there are Caucasic and Negroid genes present. The genetic constitution of Matambú differs from that of the other Amerindian groups such as the Guaymí, from Chibeha stock, which supports the hypothesis of a Mesoamerican origin.